Pengaruh Green Investment dan Good Corporate Governance terhadap Pengungkapan Emisi Karbon - Nur Zahra Luthfiani; Anike Putri; Kaca Dian Meila (Pusat Riset dan Inovasi Nasional, 2026)
The high carbon emissions produced by companies in the energy sector in Indonesia have not been accompanied by an adequate level of transparency through carbon emissions disclosure, making it an important issue in the context of sustainability. This study aims to analyze the effect of green investment and good corporate governance on carbon emissions disclosure in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. The dependent variable in this study is carbon emissions disclosure, while the independent variables include green investment and good corporate governance. This study uses a quantitative approach with secondary data obtained through purposive sampling, in the form of 50 annual reports and sustainability reports accessed from the official websites of the IDX and related companies. Data processing and testing were carried out using the Eviews 13 application with an i-random effect model. The analysis stages included descriptive statistics, panel data regression model selection, classical assumption testing, correlation coefficient testing, determination coefficient testing, and hypothesis testing. The results of the study show that green investment has no effect on carbon emission disclosure. Meanwhile, good corporate governance has an effect on carbon emission disclosure. Simultaneously, green investment and good corporate governance are proven to have an effect on carbon emission disclosure.